What accounts for the rise of low self-rated health during the recent economic crisis in Europe? - Michal Brzezinski (BMC, 2019)
Abstract Background A growing literature investigates health effects of the recent economic crisis. This study examines how different economic mechanisms affected low self-rated health (SRH) in Europe over the crisis period (2008-2011). We measure changes in low SRH over 2008-2011 and analyze how they are accounted for by changes in household income levels and income distribution (income poverty, income inequality), labour market developments (increasing unemployment, falling employment, changes in labour market inactivity), and non-income poverty (material deprivation). Methods We use balanced panel data for 2008-2011 covering 26 European countries and 43,456 participants. The data come from longitudinal 2011 European Union Statistics on Income and Living Conditions (EU-SILC) database. Increases in low SRH incidence over time are decomposed into the contributions of changes in the distribution of covariates and changes in returns to the covariates. Main covariates include household income and its distribution, labour market developments, and non-income poverty (material deprivation). The decompositions are performed using a detailed non-linear multivariate regression-based decomposition methodology. Results Low SRH incidence increased in Europe during the crisis by almost 2 percentage points, and by 3.7 percentage points in case of the Baltic countries. Decomposition analysis shows that: 1) decreasing household incomes and changing income distribution had no impact on low SRH incidence, 2) rise of material deprivation accounts for a significant portion (12%) of the overall growth in low SRH rates (27% for the Baltic countries), 3) decreasing levels of full-time and part-time employment as well as transitions to unemployment, economic inactivity, disability, or retirement account jointly for about 21% of the rise in low SRH in Europe (73% for Baltic countries). Conclusion Together, the recession-related economic factors account for about 33% of the increase in low SRH incidence in Europe during the crisis, and for about 100% of the increase in the Baltic countries. Public health policy during recessions should focus also on reducing material deprivation through free or subsidized access to public services, public housing, and other means.